Critics of Human Rights from a Historical Perspective - Bulgan, Birden Güngören (Filozofia Publiczna i Edukacja Demokratyczna, 2015)
Implementation of human rights is often criticized because it is perceived as being imposed on the rest of the world. In this case, human rights start to be seen as a sole abstraction, an empty word. What are the theoretical arguments of these critics and can we determine any historical grounds for them? In this paper, I will try to point at similar critics after the French Revolution – like that of the Historical School and Hegel – and try to show if some of these critics are still relevant. And I will compare these critics with contemporary arguments of cultural relativists. There are different streams and categorizations of human rights theories in today’s world. What differentiates them is basically the source of the human rights. After the French Revolution, the historical school had criticized the individuation and Hegel had criticized the formal freedom which was, according to him, a consequence of the Revolution. In this context Hegel drew a distinction between real freedom and formal freedom. Besides the theory of sources, the theories of implementation such as human rights as a model of learning, human rights as a result of an historical process are worth attention. The crucial point is about integrating human rights as an inner process and not to use them as a tool for intervention in other countries, which we observe in today’s world. And this is the exact point why I find the discussion of the sources more important. This discussion can help us to show how the inner evaluation of a society makes the realization of human rights possible and how we can avoid the above mentioned abstraction and misuse.